2010
DOI: 10.1016/j.jvs.2010.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Dual Antiplatelet Therapy in Patients Undergoing Surgery for Critical Limb Ischemia

Abstract: et al. Br J Surg 2010;97:650-6.Conclusion: There are no differences between sclerotherapy results in patients treated for truncal varices with foam sclerotherapy regardless of whether compression therapy after the procedure is used for 1 or 5 days.Summary: There are no data on the optimal bandaging regimen after foam sclerotherapy for truncal varices. In Great Britain, 80% of the members of the Vascular Society of Great Britain and Ireland responding to a questionnaire, and who treated patients with sclerother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Quite interestingly, it was observed that, while reducing the transfusion probability, simply increasing the Hb value had a negative impact on the Gombotz prises a comprehensive assessment of the hemostasis, treatment stop with a hemostatically active substance well ahead of the surgery, normothermia, a well-balanced acid-base balance, and a stable circulation. The widely used dual-mode antiplatelet therapy has been shown to be associated with an increased risk of spontaneous or perioperative bleedings [38]. This, however, must be carefully weighed against the then increased thrombotic risk of, e.g., implanted stents [39].…”
Section: Anemia Caused By Chronic Diseasementioning
confidence: 99%
“…Quite interestingly, it was observed that, while reducing the transfusion probability, simply increasing the Hb value had a negative impact on the Gombotz prises a comprehensive assessment of the hemostasis, treatment stop with a hemostatically active substance well ahead of the surgery, normothermia, a well-balanced acid-base balance, and a stable circulation. The widely used dual-mode antiplatelet therapy has been shown to be associated with an increased risk of spontaneous or perioperative bleedings [38]. This, however, must be carefully weighed against the then increased thrombotic risk of, e.g., implanted stents [39].…”
Section: Anemia Caused By Chronic Diseasementioning
confidence: 99%
“…Robust data on the bleeding risk associated with dual antiplatelet therapy during major non-cardiac surgery are lacking. In one randomised trial of 108 patients undergoing major vascular surgery, there was no increase in major or minor bleeding but a greater need for blood transfusion, with aspirin and clopidogrel compared to aspirin alone (16). Bridging with low molecular weight heparin appears to be associated with increased bleeding and worse ischaemic outcomes and is not recommended (17).…”
Section: "Dear Colleague This 68 Year Old Diabetic Lady Recently Undmentioning
confidence: 99%
“…In the overall population, DAPT showed no significant benefit over aspirin in preventing index graft occlusion, revascularization, above-ankle amputation of target limb, or death (HR: 0.98; 95% CI: 0.78-1.23), although subset analysis showed significant benefit in patients receiving prosthetic grafts (HR: 0.65; 95% CI: 0.45-0.95). Burdess et al [41] studied DAPT in CLI patients receiving bypass surgery or amputation, and randomized 108 patients to receive aspirin þ clopidogrel or aspirin þ placebo. The study was designed to examine platelet activation rates and bleeding risk of DAPT use in these high-risk surgical candidates.…”
Section: Dual Antiplatelet Therapy For the Secondary Prevention Of Vamentioning
confidence: 99%